Historical Accounts Of Natural Disasters In The Nusantara Archipelago: Local Wisdom And Societal Adaptations For Sustainability - Hadi Mulyana; Ming Kiri; Luc Bernard (Yayasan Adra Karima Hubbi, 2025)
Background. This study explores the rich historical records of natural disasters in the Nusantara Archipelago, focusing on the indigenous knowledge and societal adaptations that have ensured community resilience over centuries. Purpose. The research is motivated by a growing need to integrate historical and cultural perspectives into modern disaster management strategies, recognizing the value of pre-existing, community-driven solutions. The primary goal is to identify and analyze traditional coping mechanisms, governance structures, and belief systems that enabled societies to mitigate risks, respond effectively, and recover sustainably from natural hazards. Method. Employing a qualitative, historical approach, this research utilizes a variety of primary and secondary sources, including ancient texts, folk tales, colonial archives, and archaeological data. The analysis centers on case studies of significant events, such as volcanic eruptions, tsunamis, and earthquakes, to reconstruct the societal responses. Results. The findings reveal a sophisticated system of local wisdom, including sasi (traditional resource management) and simbur cahaya (traditional warning systems), deeply embedded in the cultural fabric. These practices fostered community cohesion and a profound respect for the environment. Conclusion. The conclusion highlights that these historical adaptations offer invaluable lessons for developing sustainable and culturally sensitive disaster resilience policies today.